KARAKTERISTIK RADIOLOGIS, STATUS INFEKSI HEPATITIS, DAN KADAR ALPHA-FETOPROTEIN PASIEN HEPATOCELLULAR CARCINOMA DI SAMARINDA - Abdillah, Muhammad Razaq; Rachmi, Eva; Murti, Sinta (ITKES Wiyata Husada Samarinda, 2023)
Hepatocellular Carcinoma (HCC) is a liver cancer with a high mortality rate. Hepatitis virus infection is the main factor contributing to HCC. However, there are changes in the epidemiology of HCC related to hepatitis infection. Serum Alpha-fetoprotein (AFP) examination and radiology are recommended examinations for diagnosis in Indonesia to determine the radiological characteristics of hepatitis infection status, and AFP levels in HCC patients at Abdoel Wahab Sjahranie Hospital. This study used a cross-sectional design. The data source used medical records. The samples of this study were all patients diagnosed with HCC and took samples using purposive sampling technique. The results showed that HCC patients tend to have large tumor sizes, multiple nodules, vascular invasion, hepatitis infection status, and high AFP levels. This study concludes that the majority of HCC patients at Abdoel Wahab Sjahranie Hospital have characteristics of hepatitis infection status, radiological images in the form of large tumor size, multiple nodules, and vascular invasion, as well as high AFP levels.